Could Endothelin-1 Be a Promising Neurohormonal Biomarker in Acute Heart Failure? - Bianca-Ana Dmour; Alexandru Dan Costache; Awad Dmour; Bogdan Huzum; Ștefania Teodora Duca; Adriana Chetran; Radu Ștefan Miftode; Irina Afrăsânie; Cristina Tuchiluș; Corina Maria Cianga; Gina Botnariu; Lăcrămioara Ionela Șerban; et al. (Diagnostics, 2023)
Acute heart failure (AHF) is a life-threatening condition with high morbidity and mortality. Even though this pathology has been extensively researched, there are still challenges in establishing an accurate and early diagnosis, determining the long- and short-term prognosis and choosing a targeted therapeutic strategy. The use of reliable biomarkers to support clinical judgment has been shown to improve the management of AHF patients. Despite a large pool of interesting candidate biomarkers, endothelin-1 (ET-1) appears to be involved in multiple aspects of AHF pathogenesis that include neurohormonal activation, cardiac remodeling, endothelial dysfunction, inflammation, atherosclerosis and alteration of the renal function. Since its discovery, numerous studies have shown that the level of ET-1 is associated with the severity of symptoms and cardiac dysfunction in this pathology. The purpose of this paper is to review the existing information on ET-1 and answer the question of whether this neurohormone could be a promising biomarker in AHF.